Importance of Sex Education Since Early Age for Preventing Sexual Harassment - Christofora Megawati Tirtawinata (Humaniora, 2016)
Lack of sex education in children could cause the violence or sexual abuse done by adults. Parents should give the lesson about early sex education to the children so that they had the right knowledge about it and knew how to treat and look after it. The method in this research was a discourse analysis of the literature in which the readings were taken in context with the research topic. Besides that, it included the observations and everyday practical experience in social life. This article described the notion of sex education, the impact of sexual harassment, the importance of sex education for children, and who would be responsible for sex education for the children. The research finds that through the moral education and faith to God, the children are expected to get protection from sexual abuse, so the nation's children as successor generation get mentally active.